Early large vessel systemic vasculitis in adults. Issue 4 (August 2019) - González-Gay, Miguel A.; Prieto-Peña, Diana; Martínez-Rodríguez, Isabel; Calderon-Goercke, Mónica; Banzo, Ignacio; Blanco, Ricardo; Castañeda, Santos
Abstract: Giant cell arteritis (GCA) is the most common vasculitis in individuals older than 50 years in Western countries. In addition to the typical pattern of cranial ischemic manifestations, large vessel vasculitis (LVV) involvement has emerged as a common feature of GCA. Patients with predominant LVV manifestations differ from those with the cranial pattern. They are usually affected at a younger age and often have nonspecific manifestations such as constitutional syndrome, fever of unknown origin, or refractory/atypical polymyalgia rheumatica (PMR). In these patients, cranial manifestations are often absent. Furthermore, patients with isolated PMR should be followed up because of the potential risk of severe vascular complications in the setting of an underlying GCA. Whereas temporal artery biopsy and/or color duplex ultrasound of the temporal arteries is useful for the diagnosis of cranial GCA, Doppler sonography of the subclavian and axillary arteries, fluorine-18-fluorodeoxyglucose–positron emission tomography/computed tomography, magnetic resonance, and computed tomography-angiography are very useful to identify the presence of LVV, and they may play a potential role in the follow-up of these patients.